Time-dependent behaviors of energy piles embedded in multilayered saturated transversely isotropic soils - Yongzhi Zhao; Zhenming Shi; Zhiyong Ai (Underground Space)
This paper presents a solution for the time-dependent behaviors of energy piles embedded in transversely isotropic soils, which considers the mechanical and thermal consolidation. By using the transformed differential quadrature method, kernel functions of coupled thermal-hydro-mechanical solution on the soil-energy pile interface are obtained and the boundary integration is conducted. Then, the energy pile is discretized into finite elements. After introducing the displacement coordination and boundary conditions, matrix equations to reflect the interaction between the surrounding soils and energy piles are formulated and solved. Since the consolidation is considered, the solution for energy pile behaviors with time including displacements and thermal stresses are achieved. Computational results are compared with data of existed literatures and field tests to validate the theory in this study. Finally, numerical examples are conducted to discuss the effects of transverse isotropy of soils, consolidation process and the length-diameter ratio of the energy pile.